Tourism Development In Uzbekistan. (Zien Journal of Social Sciences and Humanities, 2026)
Tourism is a key sector contributing to economic growth, regional development, and employment generation. This article analyzes the current state of the tourism sector in Uzbekistan and examines the main factors influencing its development. The research findings indicate that, despite the growth in tourist flows and the volume of tourism services, the share of tourism in the country’s gross domestic product remains below the global average. Insufficient infrastructure development, a shortage of qualified personnel, a low level of digitalization, and limited diversification of tourism products have been identified as the main challenges hindering the sustainable development of the sector. These circumstances highlight the need for further reforms in the tourism industry, the extensive adoption of digital technologies, and the implementation of comprehensive measures aimed at enhancing its competitiveness